Immunology of root resorption: A literature review - Silva Luciano; Guimaraes Carolina; Santos Roberto (Wolters Kluwer Medknow Publications, 2008)
Root resorption seems to be related to a complex combination of mechanical factors and biological activity, which comprehends the role of immunologic structures including specialized cells. The aim of this research was to explain the development of the process - from mineralization to the destruction of hard tissues - and the possible relationship between root resorption and immunology, along with discussing current concepts described in the literature.